(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Silver nanoparticles (AgNPs) have a wide range of potential applications and can be produced in an environmentally sustainable and friendly manner using the dry biomass of the green alga Chlorella ellipsoidea. This paper aims to comprehensively investigate the photophysical properties, catalytic potential, and antibacterial activity of AgNPs synthesized through this method. In the realm of photophysics, the characteristics of AgNPs such as absorbance, fluorescence, and surface plasmon resonance are analyzed in detail to gain insights into their optical behavior. Understanding these properties is crucial for elucidating the interactions of AgNPs with light, which underpins their applications in various fields including sensors, imaging, and optoelectronics. Moreover, the catalytic activity of AgNPs is explored across different chemical reactions, highlighting their potential as catalysts. Due to their high surface area to volume ratio and unique surface properties, AgNPs exhibit catalytic capabilities in reactions such as reduction, oxidation, and hydrogenation, thus finding applications in green chemistry and industrial processes. Furthermore, the antibacterial efficacy of AgNPs against pathogenic microorganisms is evaluated, emphasizing their role as potent antibacterial agents. AgNPs possess inherent antimicrobial properties attributed to their small size and high surface area, which enable them to interact with bacterial cell membranes, disrupt cellular processes, and inhibit bacterial growth. This antimicrobial activity makes AgNPs promising candidates for various biomedical applications, including wound dressings, antimicrobial coatings, and drug delivery systems. Overall, this study provides valuable insights into the multifaceted applications of AgNPs synthesized using dry biomass of Chlorella ellipsoidea, showcasing their potential in photophysics, catalysis, and antibacterial activity. By leveraging the benefits of green synthesis and exploring the diverse properties of AgNPs, this research contributes to the advancement of green nanotechnology and the development of sustainable nanoparticle-based technologies.